Chloride Penetration into Fiber Reinforced Concrete under Static and Cyclic Compressive Loading - Antoni Antoni (Civil Engineering Dimension, 2008)
The effect of loading on the chloride penetration into plain concrete (PC) and fiber reinforced concrete (FRC) was studied experimentally by using modified NT Build 492 – Non-steady state chloride migration test that include the application of loading on the specimen during the test. Three types of polypropylene fibers with different lengths and shapes were used. The concretes were tested for chloride penetration at different stress ratios under static and cyclic loading. The results of the static loading showed that there was a slight reduction in the chloride penetration under low level of compressive stress while an increase in the chloride penetration was found at higher stress level. There are significance difference in chloride penetration behavior of the plain concrete, long fiber FRC and short fiber FRC. Chloride penetration increased even more at cyclic loading conditions showing difference behavior of FRC and PC at difference number of cycle and load level.